Policing public transportation: an environmental and procedural evaluation of bus stops - Kooi, Brandon Robert (Criminal justice recent scholarship, 2007)
Review of the literature -- Evolving theoretical discussion -- Drilling down the data -- Preparing to test collective efficacy -- Preparing to compare neighborhood locations -- Systematically observing hot spot bus stops -- Mapping crime incidents -- Testing informal social control -- Comparing bus stop and non-bus stop locations -- Observations of hot spot bus stops -- Conclusions and recommendations